2017
DOI: 10.18821/0023-2149-2017-95-3-238-244
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines and signaling pathways in peripheral blood mononuclear cells in patients with coronary artery disease

Abstract: Aim. To determine content of mononuclear ells (MNC) in peripheral blood of patients with coronary heart disease (CHD) and factors responsible for their functional state and cytokine production. Materials and methods. Concentration of proteinkinases JNK1/2, ERK1/2, MAPK38, AKT1, JAK2, FAK, AMPK, p70S6K, STAT3, STAT5B and STAT6 was determined in MNC lysate by immune-enzyme assay. Interleukin 1β, 2, 4 and y-interferon levels were measured in blood sera. Results. In patients with angina of effort and unstable angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…Here we found that DLT decreased the expression level of EGFR in the myocardium of CHD rats, which may reduce cellular proliferation and differentiation. STAT5B, a member of the STATs protein family, is mainly involved in immune–inflammatory reactions and regulates cell proliferation, differentiation, and apoptosis [ 28 ]. Studies have shown that active STAT5B can activate the differentiation and generation of adipocytes through the mediation of peroxisome proliferator-activated receptor γ [ 29 , 30 ], thereby slowing the blood flow rate and accelerating plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that DLT decreased the expression level of EGFR in the myocardium of CHD rats, which may reduce cellular proliferation and differentiation. STAT5B, a member of the STATs protein family, is mainly involved in immune–inflammatory reactions and regulates cell proliferation, differentiation, and apoptosis [ 28 ]. Studies have shown that active STAT5B can activate the differentiation and generation of adipocytes through the mediation of peroxisome proliferator-activated receptor γ [ 29 , 30 ], thereby slowing the blood flow rate and accelerating plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Исследование проводили с использованием реагентов фирмы BenderMedSystems (Австрия). Забор крови для исследования проводили натощак в утренние часы [8].…”
Section: Discussionunclassified
“…В прогрессировании АГ также немаловажное значение имеет нарушение межклеточных эндотелиальных взаимодействий, опосредованных VE-кадгерином, провоспалительная активация эндотелиоцитов, сопровождающаяся повышением экспрессии молекул адгезии, в частности, ICAM-1, VCAM-1, Е-селектина и т.п. [5][6][7][8][9]. Показано, что провоспалительная активация эндотелия, а также иммунокомпетентных клеток периферической крови поддерживается компонентами РААС, в частности АТ II, что также определяется активацией AT1R и опосредуется внутриклеточной активацией G-белков [10,11].…”
Section: Introductionunclassified